ETHNOPEDAGOGY: SUNDANESE LEADERSHIP VALUES: Ethnopedagogy, Sundanese leadership values,. - Ali Ali Anwar; Jajang Hendar Hendrawan (Jurnal Ilmu Kesejahteraan Sosial HUMANITAS, 2019)
This study is conducted due to the increasing tendency of degradation in leadership attitude and behavior among the people in the society. Such degradation of leardership attitude and behavior, as shown both in efforts in becoming a leader and after being a leader, goes against the core values of the past leaders. Such a condition results from the society that has ignored the cultural values that uphold ethics and the harmony of life with nature. As a result, this studi is aimed to reveal the values of local widom in Sundanese leadership by means of collecting, orienting, and interpreting the values of Sundanese local wisdom particularly in the aspect of leadership. This sudy concludes that Sundanese leadership values are derived from oral and written traditions, namely cageur (healhty), bageur (good-hearted), bener (righteous), pinter (clever), singer (adept), teger (optimistic), pangger (tenacious), cangker (strong), and wanter (confident), which are then passed on the younger generations by means of an educational process known as ethnopedagogy.